2014
DOI: 10.1097/pep.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Strength, Joint Range of Motion, and Gait in Children and Adolescents With Osteogenesis Imperfecta

Abstract: Features vary according to OI type. Moderate and severe forms of OI are associated with greater functional limitation, influenced by fracture history, which negatively affects the acquisition and level of ambulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 48 publications
4
26
0
3
Order By: Relevance
“…A recent cross-sectional study of 62 children and adolescents with varying types of OI demonstrated that moderate and severe forms of OI are associated with greater functional impairment, influenced by fracture history, which has a negative impact on ambulation and the ability to improve with physical therapy (30). It would be reasonable to think that the more severe the functional impairment, as in OI type III, the more dramatic the weight gain secondary to the decreased functional capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study of 62 children and adolescents with varying types of OI demonstrated that moderate and severe forms of OI are associated with greater functional impairment, influenced by fracture history, which has a negative impact on ambulation and the ability to improve with physical therapy (30). It would be reasonable to think that the more severe the functional impairment, as in OI type III, the more dramatic the weight gain secondary to the decreased functional capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Features such as long bone bowing, joint laxity, and decreased range of motion and muscle strength can lead to delayed motor milestones, reduced mobility and limitations in activities of daily living [138][139][140] . Musculoskeletal impairments are greater in individ uals with more severe phenotypes 141 (TABLE 1). Individuals with osteogenesis imperfecta type I are community ambulators, who might exhibit limitations in sports and physical function 142,143 .…”
Section: Musculoskeletal Interventionsmentioning
confidence: 99%
“…Other studies produced similar results, showing reduced mobility as a result of the presence of deformities and an increased number of fractures. This led to higher BMIs in individuals with type III OI compared with other OI types [11, 28, 29]. …”
Section: Discussionmentioning
confidence: 99%